Acute Administration of Pioglitazone Attenuates Morphine Withdrawal Syndrome in Rat: A Novel Role of Pioglitazone - Ghavimi, H.; Azarfardian, A.; Maleki-Dizaji, N.; Hassanzadeh, K.; Ghanbarzadeh, S.; Charkhpour, M. (Drug Research, 2015)
Long-term exposure to opiates such is morphine induces dependence.The purpose of the present study was to investigate the effects of the acute administration of pioglitazone, a selective agonist of peroxisome proliferator activated receptors gamma (PPAR-γ), on the morphine withdrawal syndrome in the rat.Male Wistar rats (200–250 g) were selected randomly and divided into 8 groups including 2 non-dependent groups and 6 morphine-dependent groups which were received additive doses of morphine subcutaneously at an interval of 12 h for 9 continuous days. On the ninth day, only the morning dose of morphine was injected and 2 h later, morphine withdrawal was precipitated by naloxone and then ten distinct withdrawal behaviors were recorded for 45 min. Pioglitazone (5, 10, 20 and 40 mg/kg) was gavaged 2 h before naloxone injection. It is worth noting that 1 h before the pioglitazone (40 mg/kg) gavage, GW-9662 (2 mg/kg), a selective PPAR-γ antagonist, was administrated in order to evaluate the possible role of the PPAR-γ.The results of this study showed that administration of pioglitazone (40 mg/kg) decreased all withdrawal signs and the statistical analysis indicated that pioglitazone could attenuate the total withdrawal scores significantly. Administration of GW-9662 had no significant effect on pioglitazone attenuation effect on morphine withdrawal symptoms.Taking together, it was concluded that acute oral administration of pioglitazone prevented naloxone-precipitated withdrawal symptoms and GW-9662 could not revert its effect on morphine withdrawal syndrome. It seems that pioglitazone suppresses morphine withdrawal syndrome through PPAR-γ independent mechanisms.
Keywords: pioglitazone; GW-9662; morphine withdrawal; naloxone; rat